CPA Examination: Auditing. - Meigs, Walter B.; Larsen, E.J. (The Accounting Review, 1967)
Abstract This article presents questions and answers related to the November 1996 certified public accountant (CPA) examination. For the past five years a CPA has audited the financial statements of a manufacturing company. During this period, the examination scope was limited by the client regarding the observation of the annual physical inventory. Since the CPA considered the inventories to be of material amount and he was not able to satisfy himself by other auditing procedures, he was not able to express an unqualified opinion on the financial statements in each of the five years. In his short-form report the CPA should mention his lack of observance of the January 1, 1965, inventory and his lack of application of other procedures to satisfy himself. He would then issue an unqualified opinion only as to the balance sheet at December 31,1965, and issue an unqualified opinion only as to the balance sheet at December 31, 1965 and disclaim an opinion on the results of operations.